Scientific Literacy Contributions at the Galileo Museum (Florence): Integration between Historical Heritage and Contemporary (Revista Brasileira de Pesquisa em Educação em Ciências, 2025)
The Museo Galileo, in Florence, Italy, stands out as a non-formal education settings (NFES) of great historical and scientific significance and has undeniable potential to contribute to the scientific literacy of its visitors. Based on this specific perspective, the research reported in this article seeks to highlight communication strategies between the NFES and the contemporary public. Applied in nature and with a qualitative approach, the study had exploratory, descriptive, and explanatory objectives, involving bibliographic procedures, document review, survey, case study, and participant observation. Given the museum’s diverse resources, a specific approach was chosen: a self-guided tour. Given the museum’s diverse resources, a specific approach was chosen: a self-guided tour, focusing on information about Galileo’s telescopes and the inclined plane, and a guided tour aimed at students aged 8 to 11, led by a facilitator who portrays Galileo Galilei. Referring to the specialized literature on scientific literacy, attributes related to the indicators were observed: (1) scientific, evidenced by the presentation of the apparatus, the scientific method, and science as a human construction; (2) social interface, when addressing the impacts of science on society and its relationships with economic and political factors; and (3) interaction, which is expressed physically, in the aesthetic-affective and cognitive dimensions. The conclusion is that the Museo Galileo exemplifies an NFES that combines the preservation of its historical heritage with contemporary educational demands.